2017
DOI: 10.1007/s40268-016-0171-7
|View full text |Cite
|
Sign up to set email alerts
|

Drug Exposure and the Risk of Microscopic Colitis: A Critical Update

Abstract: A variety of luminal antigens, including a wide range of drugs, have been associated with the still little-known pathophysiology of microscopic colitis (MC), with variable evidence suggesting causality. This article aims to review the aspects related to drugs as potential triggers of MC; to discuss the most commonly identified associations between drugs and MC; and to analyze the limitations of the studies currently available. A literature search was performed in PubMed combining the search terms ‘drug exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 83 publications
(94 reference statements)
1
38
0
2
Order By: Relevance
“…Previous investigators have described positive associations between antisecretory medication and microscopic colitis [9][10][11], as well as inflammatory bowel disease [6][7][8]. How could these positive associations be reconciled with the inverse (negative) associations of the present analysis?…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous investigators have described positive associations between antisecretory medication and microscopic colitis [9][10][11], as well as inflammatory bowel disease [6][7][8]. How could these positive associations be reconciled with the inverse (negative) associations of the present analysis?…”
Section: Discussionmentioning
confidence: 57%
“…Similarly, epidemiological studies have suggested that gastric acid suppression using histamine‐2 receptor antagonists (H2RAs) or PPIs is associated with an increased risk for flares and adverse outcomes, such as hospitalization and surgery, among patients with Crohn's disease and ulcerative colitis . Several potential mechanisms have been suggested to explain these associations . Experimental studies have shown that PPIs induce relaxation of intestinal smooth muscle, which in turn may affect the tight junctions between colonocytes and lead to increased paracellular permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this case was diagnosed as having lansoprazole induced collagenous colitis. Already there are many reports about relevance between PPI and collagenous colitis [5,[7][8][9]. This case had a past history of administration of rabeprazole against peptic ulcer, and there was no diarrhea during administration.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, EC cells from patients with Crohn’s disease exhibit elevated 5-HT production [ 90 ], while patients with ulcerative colitis have reduced SERT expression [ 91 ]. Use of selective serotonin reuptake inhibitors has been associated with the development of microscopic colitis [ 92 ]. Mice engineered to lack components of the serotonergic system have revealed 5-HTs participation in gut disease: TPH1 −/− mice exhibited reduced severity of chemical-induced colitis and an accompanying reduction in IL-1β, IL-6, and TNF-α [ 93 ].…”
Section: -Ht In Enteric Inflammationmentioning
confidence: 99%